The Qur'an and Gender Hermeneutics: A Comparative Study of Indonesian Transformational Muslim Feminist Approaches to Gender Verses - Bannan Naelin Najihah; Jajang A. Rohmana; Eni Zulaiha (Hanifiya: Jurnal Studi Agama-Agama, 2026)
This study examines and compares five gender-interpretation models developed by Indonesian Muslim feminist thinkers: Qirāʾah Mubādalah (Faqihuddin Abdul Qadir), Maʿrūf (Badriyah Fayumi), True Justice of Women (Nur Rofiah), contextual interpretation (Husein Muhammad), and Qur’anic Gender Writing (Nur Arfiyah Febriani). Focusing on their characteristics, convergences, differences, and contextual origins, the research analyzes how these approaches construct gender justice within Indonesia’s social reality. Grounded in theological feminism and Gadamer’s hermeneutics, it employs a qualitative-comparative method through literature study, in-depth interviews, and textual analysis of primary works and secondary sources on hermeneutics, Islamic feminism, and Qur’anic interpretation. The findings show that Indonesian transformational Muslim feminist hermeneutics is contextual, critically engages patriarchal biases in classical exegesis, and epistemologically prioritizes justice and women’s liberation. While all five thinkers share a commitment to gender justice as a divine value, they differ in hermeneutic strategies, academic orientations, social experiences, and institutional positions. The study concludes that these approaches constitute a distinct, contextual, and transformative school of Qur’anic interpretation aimed at gender justice in Indonesia.